Hubungan Dukungan Keluarga Terhadap Kesehatan Jiwa Remaja Pertengahan di SMA Widyagama Malang - Fevtikasari, Anggyta; Laksana, Kurnia; Nining Loura Sari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Middle adolescence is an important period in human development, during this period adolescents experience significant physical, emotional, and social changes so that they are vulnerable to mental health problems. Good family support can help adolescents face challenges, which can prevent adolescent mental health problems. Objective: to identify The purpose of this study was to analyze the relationship between family support and mental health of middle adolescents at SMA Widyagama Malang Methods: This article This research method uses a correlational design with a cross-sectional design. The independent variable is family support and the dependent variable is mental health. The subjects of this study were students in grades X, XI, and XII. The sampling technique used proportionate random sampling. The research sample was 87 respondents. Results: The results of statistical tests using Spearmank Rank on the difficult aspect obtained p = 0.000 (p value ≤ 0.05 means there is a correlation) and r = 0.500 (the strength of the correlation category is sufficient) on the strength aspect obtained p = 0.000 (p value ≤ 0.05 means there is a correlation) and r = 0.417 (the strength of the correlation category is sufficient). This means that there is a relationship between family support and mental health of middle-aged adolescents at SMA Widyagama Malang Conclusion: These results indicate that families play a role in maintaining adolescent mental health. The higher the family support given, the better the adolescent mental health, conversely, the lower the family support given, the worse the adolescent mental health. The results of this study are expected to make adolescents more open to their families when experiencing mental health problems and for schools to provide guidance to adolescents or their families to support adolescent mental health.